The International Association for the Study of Lung Cancer Lung Cancer Staging Project: Proposals for the Revision of the N Descriptors in the Forthcoming 8th Edition of the TNM Classification for Lung Cancer. Issue 12 (December 2015) - Asamura, Hisao; Chansky, Kari; Crowley, John; Goldstraw, Peter; Rusch, Valerie W.; Vansteenkiste, Johan F.; Watanabe, Hirokazu; Wu, Yi-Long; Zielinski, Marcin; Ball, David; Rami-Porta, Ramon
Abstract : Introduction: Nodal status is considered to be one of the most reliable indicators of the prognosis in patients with lung cancer and thus is indispensable in determining the optimal therapeutic options. We sought to determine whether the current nodal (N) descriptors should be maintained or revised for the next edition (8th) of the International Lung Cancer Staging System. Methods: The new International Association for the Study of Lung Cancer lung cancer database was created from 94, 708 patients diagnosed as having lung cancer between 1999 and 2010. Among these, 38, 910 and 31, 426 patients with non–small-cell lung carcinoma were available for an analysis of the clinical (c)N and pathological (p)N status, respectively. The anatomical location of lymph node involvement was defined by either the Naruke (for Japanese data) or American Thoracic Society (for non-Japanese data) nodal charts. Survival was calculated by the Kaplan–Meier method, and prognostic groups were assessed by a Cox regression analysis. Results: The current N0 to N3 descriptors for both the cN and pN status consistently separated prognostically distinct groups. The 5-year survival rates according to the cN and pN status were 60% and 75% (N0), 37% and 49% (N1), 23% and 36% (N2), and 9% and 20% (N3), respectively. The differences in survival between all neighboring nodal categories were highly significant for both the cN and pN status. With regard to pathological staging, additional analyses regarding the prognosis were performed by further dividing N1 into N1 at a single station (N1a) and N1 at multiple stations (N1b); N2 into N2 at a single station without N1 involvement ("skip" metastasis, N2a1), N2 at a single station with N1 involvement (N2a2), and N2 at multiple stations (N2b). The survival curves for N1b and N2a2 overlapped each other, and N2a1 had numerically a better prognosis than N1b, although the difference was not significant. Geographic difference in N-specific prognosis was observed for both c-settings and p-settings. This might have been because of the difference in the used nodal map, surgical technique, and pathologist's handling of the resected specimen. Conclusions: Current N descriptors adequately predict the prognosis and therefore should be maintained in the forthcoming staging system. Furthermore, we recommend that physicians record the number of metastatic lymph nodes (or stations) and to further classify the N category using new descriptors, such as N1a, N1b, N2a, N2b, and N3, for further testing.